Sedimentary characteristics of the Lingshui Formation in the Baodao 21-1 area of the Qiongdongnan Basin and their significance in hydrocarbon exploration - Rufeng JIANG; Licheng CAO; Xiaoliang DENG; Yunlong HE; Yaoqi JIAO; Zigui CHEN; Tao LI; Qi ZHANG (地质科技通报)
Objective The first deepwater and deep-stratum gas field was recently discovered in the Baodao 21-1 area of the Qiongdongnan Basin, which is of great significance for petroleum exploration in the deep-water area of the South China Sea. Methods Based on the newly acquired drilling-seismic data, the sedimentary characteristics of the Third Member of the Upper Oligocene Lingshui Formation and their significance in hydrocarbon exploration were analyzed in the Baodao 21-1 area. Results Bidirectional sediment provenances controlled the deposition of the Third Member of the Lingshui Formation, resulting in the early deposition of fan delta in the adjacent uplands and the late deposition of braided river delta fed by sediment sources of the Hainan Uplift on the northwest and the Shenhu Uplift on the northeast. In addition, the routes of sediment transport between steep and gentle slopes show great variability. The evolution of the sedimentary system in the Third Member of the Lingshui Formation can be divided into three stages, including the fan delta deposition in the early stage, the fan delta and braided river delta depositions in the middle stage, and the braided river delta deposition in the late stage. Correspondingly, the sediment provenances changed from the adjacent highlands in the early stage, to both adjacent highlands and Shenhu Uplift in the middle stage, and finally to both Hainan Uplift and Shenhu Uplift in the late stage. The Baodao 21-1 area is close to the hydrocarbon kitchen of the Yacheng Formation and it contains the No.12-1 Fault-Fracture systems and the tectonic-lithologic traps, favoring the petroleum accumulation. Conclusion The discovery of the Baodao 21-1 gas field is a breakthrough in deepwater petroleum exploration in China, pointing out that the fracture transition zone of marine basins is a key area for future deepwater exploration.